Sanksi Publisitas Dalam Bentuk Pidana Pengumuman Putusan Pengadilan Terhadap Korporasi Pelaku Perdagangan Orang - Ivanna Eltiara Cahyani; Amrullah, Arief; Dina Tsalits Wildana (Fakultas Hukum Universitas Andalas, 2024)
Indonesia ratified the Law Number 21 of 2007 on the Eradication of Criminal Acts of Trafficking in Persons (UUPTPPO) which contains comprehensive regulations that expand the scope of perpetrators by including corporations. Fine penalty only has a financial impact and is considered as business loss for corporations. In addition, the additional penalties provided for by the law do not have much impact on corporations as they can still operate without a license. The trend of corporations to seek maximum profit, coupled with the lack of knowledge of victims about the modes of human trafficking crimes, makes it necessary to impose additional penalties such as the announcement of the court's decision. This study aims to explain the urgency of the announcement of the court's decision as an additional penalty and to provide ideas for its implementation scheme. The research results show that the announcement of the court's decision is a formal publicity sanction that has never been applied in Indonesia. As input to fill the legal vacuum, limited formal publicity sanction mechanisms can be used as a reference for implementation. Through such a mechanism, the announcement of the court's decision is aimed at lowering the reputation and inducing government intervention.